Effect of Activity Student-Centered Experiment and Improvisation Teaching Strategy on Students’ Chemistry Achievement in Federal Capital Territory, Abuja - OMALE, Emmanuel (Ilorin Journal of Education, 2024)
The impact of Activity Student-Centered Experiment and Improvisation (ASEI) teaching approach on the academic achievement of chemistry learners in the Federal Capital Territory, Abuja was examined by the researcher. Research questions and research hypotheses were developed from the study’s research objectives. The research design used for this investigation was pretest posttest control group quasi-experimental research design. Purposive sampling was used to select 160 students from among the 1,680 SS One chemistry students that made up the study’s population. The data for the study were collected with the use of Chemistry Achievement Test (CAT) that was validated by two experts in science education and educational measurement and evaluation. The Kuder Richardson formula-21 was employed to determine the reliability of CAT and a co-efficient value of 0.89 was obtained. The data collected were analysed using descriptive statistics to answer the research questions while Analysis of Covariance (ANCOVA) was used to test the research hypotheses. The findings of the study revealed that using the ASEI method of instruction improves learners’ chemistry achievement more than the use of traditional methods. It was recommended among others that in-service and pre-service educator training programs in Nigeria should incorporate the application of the ASEI strategy for instruction by educators’ trainers. This will make it possible for educators who teach chemistry to implement category exercises that incorporate the use of the ASEI teaching strategy in their teaching process.